Kerjasama Pemerintah Indonesia dan Malaysia dalam Menangani Permasalahan TKI Ilegal - Yoseph Lentvino Satyanugra; Hermini Susiatiningsih (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2021)
This research discusses the problem of violence experienced by migrant workers, especially illegal migrant workers while working in Malaysia. The number of problems caused by illegal migrant workers due to lack of educational background, and the origin of migrant workers from families who cannot afford it, is the main reason for the existence of illegal migrant workers. This is not only troubling the Malaysian side but also the Indonesian side. Then there needs to be a continuous review of why similar cases can occur. This research aims to find out what forms of violations occur against Indonesian workers and also what steps and cooperation efforts are taken by the Indonesian government with the Malaysian state. This research uses the theory of international cooperation to explain and analyze the themes discussed in the research. The results of this research analysis can be known that international cooperation between Indonesia and Malaysia got quite good results, evidenced by the success of the MoU agreement. But when the MoU agreement has expired or expired, the results of JC, JTF and JWG performance become not maximal, arguably even unsuccessful in dealing with the problems that occur.